Neural Compensations After Lesion of the Cerebral Cortex - Bryan Kolb; Russell Brown; Alane Witt-Lajeunesse; Robbin Gibb (Neural Plasticity)
Functional improvement after cortical injury can be stimulated by various factors including experience, psychomotor stimulants, gonadal hormones, and neurotrophic factors. The, timing of the administration of these factors may be critical, however. For example, factors such as gonadal hormones, nerve growth factor, or psychomotor stimulants may act to either enhance or retard recovery, depending upon the timing of administration. Nicotine, for instance, stimulates recovery if given after an injury but is without neuroprotective effect and may actually retard recovery if it is given only preinjury. A related timing problem concerns the interaction of different treatments. For example, behavioral therapies may act, in part, via their action in stimulating the endogenous production of trophic factors. Thus, combining behavioral therapies with pharmacological administration of compounds to increase the availability of trophic factors enhances functional outcome. Finally, anatomical evidence suggests that the mechanism of action of many treatments is through changes in dendritic arborization, which presumably reflects changes in synaptic organization. Factors that enhance dendritic change stimulate functional compensation, whereas factors that retard or block dendritic change block or retard compensation.